Environmental Factors in the Production of Code-Switching in Pre-school Children: A Case study of Three Indonesian Children - Puji Siswanto; Arief Styo Nugroho; Usmaedi Usmaedi; Ade Eka Anggraini (Jurnal Pendidikan Humaniora, 2022)
Abstract: The study investigates code-switching performed by three pre-school children in Indonesia. The study employs a qualitative research methodology with an exploratory case study. The participants of the study are three pre-school children who live in a small village in Banten Province in which two languages are exposed and spoken by the majority of people in that area namely Bahasa Indonesia as the national language and Sundanese as a vernacular language. The study reveals that the code-switching utterances performed by preschool children are classified into intra and inter sentential switches.Keywords: children, code-switching, environmental, pre-school